Efficacy of ACEIs/ARBs vs CCBs on the progression of COVID‐19 patients with hypertension in Wuhan: A hospital‐based retrospective cohort study. Issue 2 (5th October 2020) - Liu, Xiulan; Liu, Yi; Chen, Keliang; Yan, Suying; Bai, Xiangrong; Li, Juan; Liu, Dong
Abstract: To evaluate the efficacy of angiotensin‐converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) vs calcium channel blockers (CCBs) on the progression of Corona Virus Disease 2019 (COVID‐19) patients with hypertension in Wuhan. This retrospective single‐center case series analyzed COVID‐19 patients with hypertension, treated with ACEIs/ARBs or CCBs at the Tongji Hospital of Wuhan City, China from 25th January to 15th March 2020. After propensity score matching analysis, 76 patients were selected into two groups. Univariate and multivariable analyses were conducted to determine factors related to improvement measures and outcome measures by Cox proportional hazard regression models. Among 157 patients with confirmed COVID‐19 combined hypertension, including 73 males and 84 females, a median age of 67.28 ± 9.11 vs 65.39 ± 10.85 years. A univariable analysis indicated that clinical classification, lymphocyte count, and interleukin‐2 receptor were associated with a lengthened negative time of nucleic acid, with a significant difference between two groups ( P  = .036). Furthermore, we found no obvious difference in nucleic acid conversion time between ACEIs/ARBs and CCBs groups (hazard ratio [HR]: 0.70; 95% confidence interval [CI]: [0.97, 3.38]; P  = .18) in the multivariable analysis as well as chest computed tomography improved time (HR: 0.73; 95% CI [0.45, 1.2]; P  = .87), and hospitalization time between ACEIs/ARBs and CCBs groups (HR: 1.06; 95% CI [0.44, 1.1]; P  = .83). Our study provided additional evidence of no obvious difference in progress and prognosis between ACEIs/ACEIs and CCBs group, which may suggest ACEIs/ARBs may have scarcely influence on increasing the clinical severe situations of COVID‐19 patients with hypertension. Highlights: 1. Antihypertensive drugs, either ACEIs/ARBs or CCBs had few effects on firstly negative nucleic acid time, firstly chest CT improved time and the hospitalization time of COVID‐19 by a cox Regression analysis. 2. ACEIs/ARBs didn't increase the risk of extended course and poor prognosis of hypertension patients with COVID‐19.